Transfer of Raman Spectra with Different Resolutions Applying Convolution with Gaussian Function - Dong, Xue-Feng; Dai, Lian-Kui (Asian Journal of Chemistry, 2012)
Calibration transfer of Raman spectra was investigated on the basis of instrument response function, which is affected by the resolution of the spectrometer. A simplified procedure is presented allowing the transfer of Raman spectra from higher to lower resolution instruments (or conditions). Needn't to measure a set of well-prepared samples to construct a statistical transfer model, the method employed in preent study, a convolution step involving a Gaussian transfer function, which theoretically describes the instrumental difference from source to target. And with the help of established methods for wavenumber calibration and relative intensity correction, an integrated algorithm for Raman spectra transfer is provided. Two spectral experiments of three analytes were performed for certification: (1) Transfer on a Fourier transform (FT) Raman spectrometer under various resolution conditions; (2) Transfer between two dispersive Raman spectrometers equipped with charge-coupled device (CCD). In almost all cases, the correlation coefficient between the measured spectra and transferred spectra could reach to 0.99. It suggested that this procedure may be applicable for all kinds of Raman spectra transfer and even works universally in other spectroscopy.